Rekonstruksi Paradigma Pembelajaran Tawhidi dalam Pendidikan Islam: Analisis Worldview dan Model Konseptual Integratif - maya yunus (Darajat: Jurnal Pendidikan Agama Islam, 2026)
Modern education faces an orientation crisis caused by the dominance of a secular paradigm that separates knowledge from spiritual values. This condition produces learners who develop cognitively but lack maturity in adab and spirituality. Existing efforts to integrate Islamic values into learning remain additive and have not touched the epistemological structure of knowledge. This article aims to: (1) analyse the worldview foundation of tawhidi learning; (2) formulate an operational conceptual model; and (3) identify its implications for educational practice. The study uses a qualitative approach with library research, supported by content analysis, philosophical analysis, and conceptual synthesis of classical and contemporary Islamic educational thought. The findings show that tawhidi learning forms an integrative paradigm that links ontological, epistemological, and axiological dimensions through five interconnected stages: intention (niyyah), knowledge as ayat, divine consciousness (muraqabah), reflection (muhasabah), and actualisation in deeds. These five dimensions form a continuous cycle that deepens the learner’s faith and knowledge. The main contribution lies in shifting the discourse from additive value integration toward worldview reconstruction as a pedagogical foundation, with practical implications for instructional design, the teacher’s role as murabbi, and assessment systems oriented toward spiritual and praxiological dimensions.